ANALISIS KESULITAN PEMAHAMAN KONSEP DAN KEMANDIRIAN BELAJAR PADA PROSES PEMBELAJARAN MATEMATIKA SELAMA PANDEMI COVID-19 - Mentari Izzati; Rizqi Amaliyakh Sholikhakh; Suwandono Suwandono (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
This study aims to describe the students' difficulty of concepts understanding  in statistical material and the relationship between conceptual understanding and self-rugulated learning of students in class VIII of SMP Negeri 1 Dukuhturi. This research is a descriptive research with a qualitative approach. The subjects in this study were 6 students of class VIII E of SMP Negeri 1 Dukuhturi, who were selected from each concept understanding using purposive sampling technique. The determination of the research subjects is based on the results of students' understanding of mathematical concepts. The data collection techniques used were tests of understanding mathematical concepts, interviews, self-regulated learning questionnaires, and documentation. The results of the study indicate that those who have a high level of conceptual understanding do not necessarily have high self-regulated learning as well. The results of the research analysis show that: 1) The difficulty of understanding mathematical concepts in statistical material, the inability to determine quartiles correctly, in relating external mathematical concepts, namely algebra and comparison materials, as well as in understanding story problems. 2) There is a correlation between understanding the concept and self-regulated learning on the subject of T1 and S2. Meanwhile, in the subjects of T2, S1, R1 and R2, there is no correlation between concept understanding and self-regulated learning of mathematics.